2011
DOI: 10.1021/ac2016823
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed Immunohistochemical Detection of Tumor Markers in Breast Cancer Tissue Using Laser Ablation Inductively Coupled Plasma Mass Spectrometry

Abstract: We optimized multiplexed immunohistochemistry (IHC) on breast cancer tissue. Up to 20 tumor markers are routinely evaluated for one patient, and thus, a common analysis results in a series of time consuming staining procedures. As an alternative, we used lanthanides for labeling of primary antibodies, which are applied in IHC. Laser ablation (LA) ICPMS was elaborated as a detection tool for multiplexed IHC of tissue sections. In this study, we optimized sample preparation steps and LA ICPMS parameters to achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
72
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 27 publications
0
72
0
Order By: Relevance
“…There are efforts to further improve the immunoassays and immunohistochemical tests for CEA [176]. Some further examples are: -carcinoembryonic antigen in lung cancer [177] -tumour markers [178] -gynecological cancer [179] -pancreatic cancer [180] -breast cancer [181,182] Brought to you by | University of Kent Authenticated Download Date | 12/14/17 7:10 PM -breast cancer differential diagnosis [183] -undifferentiated tumours [184], leukemias [185,186], and soft-tissue tumours [187] -renal neoplasms [188] -oral cancer [189] …”
Section: Cancer Markersmentioning
confidence: 99%
“…There are efforts to further improve the immunoassays and immunohistochemical tests for CEA [176]. Some further examples are: -carcinoembryonic antigen in lung cancer [177] -tumour markers [178] -gynecological cancer [179] -pancreatic cancer [180] -breast cancer [181,182] Brought to you by | University of Kent Authenticated Download Date | 12/14/17 7:10 PM -breast cancer differential diagnosis [183] -undifferentiated tumours [184], leukemias [185,186], and soft-tissue tumours [187] -renal neoplasms [188] -oral cancer [189] …”
Section: Cancer Markersmentioning
confidence: 99%
“…There are efforts to further improve the immunoassays and immunohistochemical tests for CEA [176]. Some further examples are: -carcinoembryonic antigen in lung cancer [177] -tumour markers [178] -gynecological cancer [179] -pancreatic cancer [180] -breast cancer [181,182] -breast cancer differential diagnosis [183] -undifferentiated tumours [184], leukemias [185,186], and soft-tissue tumours [187] -renal neoplasms [188] -oral cancer [189] …”
Section: Cancer Markersmentioning
confidence: 99%
“…A further application of LA-ICP-MS in this research area is the use of element-tagged immunoassays for imaging purposes, which provides a new strategy for not only mapping peptides and proteins in different types of tissues, but also for their possible quantification [13,16,88,89]. In this vein, Hutchinson et al [16] reported the imaging of amyloid precursor protein and Aβ peptide in histological sections of a transgenic mouse model of Alzheimer's disease using Eu-and Ni-coupled antibodies.…”
Section: La-icp-msmentioning
confidence: 99%
“…The analytical potential of immunohistochemistry combined with LA-ICP-MS has also been demonstrated for the imaging of cancer biomarkers [88,89]. The distributions of two breast cancer-associated proteins (MUC-1 and HER2) were studied based on multiple line scanning of tissue sections by the laser beam and the subsequent measurement of relevant Au/Ag-tagged antibodies bound to the tissue.…”
Section: La-icp-msmentioning
confidence: 99%